2018
DOI: 10.3389/fphys.2018.00334
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Hemangiomas Alter Morphometry and Impair Hemodynamics of the Abdominal Aorta and Primary Branches From Computer Simulations

Abstract: Background: The formation of hepatic hemangiomas (HH) is associated with VEGF and IL-7 that alter conduit arteries and small arterioles. To our knowledge, there are no studies to investigate the effects of HH on the hemodynamics in conduit arteries. The aim of the study is to perform morphometric and hemodynamic analysis in abdominal conduit arteries and bifurcations of HH patients and controls.Methods: Based on morphometry reconstructed from CT images, geometrical models were meshed with prismatic elements fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Hepatic cavernous hemangioma is the most common benign tumor of the liver (Yin et al, 2018), with a reported prevalence of 20% in autopsy (Bahirwani and Reddy 2008). This tumor is typically observed in females (female: male ratio = 5:1) at an average age of 50 years (Duxbury and Garden 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic cavernous hemangioma is the most common benign tumor of the liver (Yin et al, 2018), with a reported prevalence of 20% in autopsy (Bahirwani and Reddy 2008). This tumor is typically observed in females (female: male ratio = 5:1) at an average age of 50 years (Duxbury and Garden 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The expression or functionality of TRPV in BMEC forming the BBB was much less studied than in non-cerebral endothelial cells although there is growing evidence that TRP channels may have a critical role at the BBB by modulating Ca 2+ trafficking into BMEC. Dysfunctions of the BBB are increasingly recognized as a cause or a consequence in the pathophysiology of diverse brain pathologies such as stroke, neurodegenerative and psychiatric diseases ( Sweeney et al, 2019 ; Yang et al, 2019 ; Kealy et al, 2020 ; Yu et al, 2020 ). A dysfunctional BBB can thus be targeted with new drug candidates, which would be a promising way for treating brain pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the incidence of HH in the general population is 5-20% [16][17][18] . Statistical analyses of data extracted from the physical examination reports of 670,000 healthy individuals in China revealed that the incidence of HH was approximately 1.5%, and the male to female ratio was approximately 1.3:1.…”
Section: Discussionmentioning
confidence: 99%